Liraglutide Nano-Preparation on Perioperative Neurocognitive Dysfunction in Aged Mice - Zhang, Jiejie; Song, Jie; Gu, Tianyu; Yang, Jianping; Cai, Xuejiao; Cai, Mengmeng; Sun, Jiafeng (Cellular and Molecular Biology, 2022)
At present, there is not enough research about the application of liraglutide nano preparations in perioperative neurocognitive dysfunction. Therefore, the purpose of this study is the mechanism of the effect of liraglutide nano preparations on perioperative neurocognitive dysfunction in aged mice. In this study, 140 male SD rats aged 6-8 weeks were used as the research object, and were divided into 4 groups (n=24) according to the random number table method, which were group C (control group), group S (model group), and treatment. Group (low-dose liraglutide pretreated control group) and DS2 group (high-dose liraglutide pretreated control group) were treated with liraglutide anesthesia to establish a cognitive dysfunction model. Morris water maze experiment was conducted 4 days after anesthesia to compare the escape latency and the number of crossings of the original platform in each group; after 4 days of anesthesia, 18 old mice were randomly selected from each group for fluorescence quantitative polymerase chain reaction (RealTimePCR) and protein Western blotting (Western.Blot) was used to determine the mRNA and protein levels of Caspase-3, Bax and Bcl-2 in the hippocampus; the remaining 6 old mice in each group were taken to observe the pathological changes of the hippocampus neurons by transmission electron microscopy . Compared with saline-treated group, the levels of NF-KB, TNF-a and IL-1β protein in mice treated with liraglutide decreased and IkB increased significantly (p<0.05). Liraglutide intervention may alleviate non-alcoholic fatty liver in diabetic mice by reducing the expression of inflammatory genes in liver tissue, thereby improving neurocognitive dysfunction in mice.